Ser ou não ser? eis a questão: uma investigação sobre a vulnerabilidade dos consumidores - Silva, Arielle Pinto (2011)
This dissertation aims to contribute to construction of scale for measuring the consumer vulnerability in consumption situation. This goal is based on the importance of the comprehension of the subject for consumer s welfare, especially for consumers identified as most likely to experience a harm situation. The vulnerability subject belongs to the Marketing and Society discipline which associates marketing as an institution in order to generate welfare to society. This research aimed to (1) understand the consumer vulnerability (2) identify the dimension of the consumer s vulnerabilities (3) Identify differences and similarities between vulnerable consumer groups and, (4) define indicators for the measurement scale. We have used the theoretical model of comprehension of the vulnerability of Baker et al. (2005) and the bibliographic research collected in order to build a guide for interviews having as subjects groups of individuals considered by the literature as vulnerable. Those individuals have been interviewed and the analysis of the results as well as the theoretical reference generated the scale items. The content analysis have identified six dimensions related to the vulnerability phenomenon, which are: vulnerability experience, individual characteristics, individual state, external and structural conditions, vulnerability experience inside a consumption context, and finaly, consumer response. By these dimensions items have been generated which generated the scale. We have generated in total 69 items for scale. Final considerations discuss the findings of the research, it s theoretic s and general s implications, as well as suggestions to continue the research about this subject.